PENGEMBANGAN HANDOUT IPA FISIKA BERBENTUK KOMIK BERDASARKAN MODEL PBM UNTUK PEMBELAJARAN SISWA KELAS IX SEMESTER I PADA KONSEP KELISTRIKAN DI SMP N 1 PANCUNG SOAL - Ridha Lifani Safitri (PILLAR OF PHYSICS EDUCATION, 2014)
This research is motivated by Physics learning is still centered on the teacher, and the limited teaching materials that can be used by students. To complement the shortage of teaching materials should be developed which is able to provide hands-on experience for students. The purpose of this research is to produce a Physics handouts with comic form based on Problem Based Learning models and to determine the validity, practicality and effectiveness of this product. The type of this research is Research and Development (R & D). Based on data analysis we can concluded; first, a description of the product consists of a cover design, identity handouts, character recognition, and a description of the material, second, the validity of the handout 82,6, third, practicality according to the teacher 9.25 and 89.3 by the students practical value, fourth, handouts effective in improving student learning outcomes